The Informal Networks in Food Procurement by Older People: A Cross European Comparison - Turrini, Aida (2010)
Healthy dietary profiles contribute to successful aging, and dietary intake is dependent upon food procurement capabilities. Both formal and informal social networks can contribute to grocery shopping capabilities and methods of food procurement. This investigation explores the role of informal networks in food procurement methods among adults aged 65 years and older, and compares differences across eight European countries. Food shopping ways (FSW), identified by quantitative analysis (cluster analysis and correspondence analysis), guided the content qualitative analysis which was carried out addressing three main research questions addressing food shopping routines, feelings of dependency and needs of informal support for shopping, and differences between past and present food shopping behaviours. Living circumstances influence food shopping habits. Informal networks differed between two groups of individuals: those living alone and those living with others. Gender differences emerged in shopping pleasure. Geographical factors were associated with preference for shopping companions, attitudes toward receiving support, and availability of a car for shopping. The importance of living circumstances (i.e., alone vs. with others) in FSW was revealed. Informal social networks may play an important role in public health and welfare policies, particularly given the increase in this demographic group. Assistance with grocery shopping and the availability of trained personnel could widen informal networks, and effective informal networks may be an important supportive service for older adults. The comparison across countries highlighted relationships between food procurement capabilities and social networks. These findings may be used to develop resources to better meet the nutritional needs of older adults.